2014
DOI: 10.2478/pomr-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Prediction for Hard Chine Hulls in the Pre-Planing Regime

Abstract: A mathematical representation of calm-water resistance for contemporary planing hull forms based on the USCG and TUNS Series is presented. Regression analysis and artificial neural network (ANN) techniques are used to establish, respectively, Simple and Complex mathematical models. For the Simple model, resistance is the dependent variable (actually R/∆ for standard displacement of ∆ = 100000 lb), while the Froude number based on volume (F nV ) and slenderness ration (L/V 1/3 ) are the independent variables. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…To obtain a lower resistance, one must be able to obtain hydrodynamic lift at the lowest possible speed. Research results on semi-displacement hull optimization are reported in [35][36][37][38]; they are mainly experimental and the results in the form of regression formulas are very useful at a preliminary design stage and highlight the effect of hull geometry and CG position.…”
Section: Hydrodynamic Issues Related To the Zero-emission Modementioning
confidence: 99%
“…To obtain a lower resistance, one must be able to obtain hydrodynamic lift at the lowest possible speed. Research results on semi-displacement hull optimization are reported in [35][36][37][38]; they are mainly experimental and the results in the form of regression formulas are very useful at a preliminary design stage and highlight the effect of hull geometry and CG position.…”
Section: Hydrodynamic Issues Related To the Zero-emission Modementioning
confidence: 99%
“…Some other research activities related to the prediction of dynamic equilibrium of planing hulls have been conducted with the emphasis on warped hull planing hulls ( (Bertorello and Olivero (2007); Schachter et al (2016)). In recent years, Radojcic et al (2014a and developed relations for the resistance of such a hull by applying artificial neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Their results included pressure distribution, trim angle, rise of centre of gravity and resistance at various speeds [11]. Recently, Radojcic et al [12] presented a mathematical model of calm-water resistance for contemporary planing hull forms based on the USCG and TUNS series. They derived two speed -dependent mathematical models, simple and complex, to evaluate the calm-water resistance.…”
Section: Literature Reviewmentioning
confidence: 99%